IMPLEMENTASI TEORI KECERDASAN GANDA DALAM PEMBELAJARAN BAHASA INGGRIS: KAJIAN PENDEKATAN MULTIDISIPLINER - Md. Yudyantara Risadi; Putu Budi Adnyana; I Putu Wisna Ariawan; I Gede Astra Wesnawa (Institut Agama Hindu Negeri Gde Pudja Mataram, 2026)
This study aims to analyse the implementation of Multiple Intelligences (MI) theory in English language education through a multidisciplinary approach. The investigation is motivated by the need for more inclusive instructional models amidst the prevailing dominance of educational systems that prioritize singular cognitive abilities. Employing a literature review methodology, the study examines nationally indexed (SINTA) and internationally indexed (Scopus) articles to identify patterns, relevance, and contributions of MI theory to the enhancement of English language learning quality. The analysis reveals that MI-based instruction significantly improves students’ motivation, engagement, and learning outcomes by aligning pedagogical strategies with individual intelligence profiles. Furthermore, the theory reinforces cultural, social, and humanistic values within educational contexts. Theoretically, this research affirms that MI is not merely a theoretical framework but a humanistic paradigm in language education. The implications suggest that English language instruction should be oriented toward the development of multidimensional potentials and instructional differentiation that respects learner diversity.